Middle-range theories of land system change. (November 2018) - Meyfroidt, P.; Roy Chowdhury, R.; de Bremond, A.; Ellis, E.C.; Erb, K.-H.; Filatova, T.; Garrett, R.D.; Grove, J.M.; Heinimann, A.; Kuemmerle, T.; Kull, C.A.; Lambin, E.F.; et al.
Highlights: Landsystem science produced many empirical results but lacks progress in theory. We review theories on causes of changes in land use extent and intensity. We synthesize middle-range theories of systemic land system processes. Theories of land-use spillovers (land sparing and rebound effects with intensification, leakage). Theories of land-use transitions (structural non-linear changes, including forest transition). Abstract: Changes in land systems generate many sustainability challenges. Identifying more sustainable land-use alternatives requires solid theoretical foundations on the causes of land-use/cover changes. Land system science is a maturing field that has produced a wealth of methodological innovations and empirical observations on land-cover and land-use change, from patterns and processes to causes. We take stock of this knowledge by reviewing and synthesizing the theories that explain the causal mechanisms of land-use change, including systemic linkages between distant land-use changes, with a focus on agriculture and forestry processes. We first review theories explaining changes in land-use extent, such as agricultural expansion, deforestation, frontier development, and land abandonment, and changes in land-use intensity, such as agricultural intensification and disintensification. We then synthesize theories of higher-level land system change processes, focusing on: (i) land-use spillovers, including land sparing and rebound effects with intensification, leakage, indirect land-use change, and land-use displacement, and (ii) land-use transitions, defined as structural non-linear changes in land systems, including forest transitions. Theories focusing on the causes of land system changes span theoretically and epistemologically disparate knowledge domains and build from deductive, abductive, and inductive approaches. A grand, integrated theory of land system change remains elusive. Yet, we show that middle-range theories – defined here as contextual generalizations that describe chains of causal mechanisms explaining a well-bounded range of phenomena, as well as the conditions that trigger, enable, or prevent these causal chains –, provide a path towards generalized knowledge of land systems. This knowledge can support progress towards sustainable social-ecological systems.